Report on Making Business Legality through OSS MSMEs in Lempuyangan Village - Epsilandri Septyarini; Tyagita Dianingtyas Sudibyo; Ansri Jayanti; Tasrim; Kurniawan, Angga (JOURNAL INCLUSIVE SOCIETY COMMUNITY SERVIES, 2023)
Business legality is approval for the implementation of business activities given to individuals or groups of people from the authorized parties. One form of business legality is NIB (Business Identification Number). The existence of NIB can provide benefits for entrepreneurs, especially in terms of obtaining assistance from the government. There are still MSMEs that do not know or have received an NIB certificate, which is the main problem that is often encountered in Lempuyangan Village. This community service program aims to provide understanding, training and mentoring business legality in the form of online NIB via the Online Single Submission (OSS) application for MSMEs in Lempuyangan Village. MSMEs are targets in the NIB formation program. The methods used in this mentoring program are Research, Action and Participation. The result of this assistance is that MSMEs have knowledge about NIB, obtain an NIB certificate, which can then be used to develop their business, such as applying for people's business credit (KUR) and guidance from the government.